2007
DOI: 10.1007/s00296-007-0480-9
|View full text |Cite
|
Sign up to set email alerts
|

Leptin serum levels in rheumatoid arthritis patients: relation to disease duration and activity

Abstract: Leptin is a peptide hormone with the tertiary structure of a cytokine, which not only regulates body weight by inhibiting food intake, but also modulates inflammatory and immune responses. The aim of the study was to investigate if there are connections between leptin concentrations and parameters of nutritional status and disease activity in a group of rheumatoid arthritis (RA) patients. The study group consisted of 37 patients. The mean leptin serum concentration was significantly higher in women than in men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 26 publications
7
47
0
1
Order By: Relevance
“…There was also a tendency of correlation between leptin level and cystatin C concentration (novel renal function parameter). The results suggested, that leptin levels were increased in pts with higher disease activity and the risk of progressive joint destruction [12]. 9 In the present study we confirmed the observation of proinflammatory leptin function in the course of RA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There was also a tendency of correlation between leptin level and cystatin C concentration (novel renal function parameter). The results suggested, that leptin levels were increased in pts with higher disease activity and the risk of progressive joint destruction [12]. 9 In the present study we confirmed the observation of proinflammatory leptin function in the course of RA.…”
Section: Discussionsupporting
confidence: 89%
“…Leptin concentrations were found to be similar [12,13,14,15,16], lower [17], or higher [18,19] in comparison with healthy controls or with pts with osteoarthritis (OA) [20]. Plasma levels of adiponectin, leptin and visfatin were found to be increased in RA pts [21] or did not differ significantly in RA pts and in healthy controls [22].…”
Section: Introductionmentioning
confidence: 99%
“…In one study, 75 serum leptin concentrations were higher in patients with erosive RA. Another study has shown that concentrations of leptin in synovial fluid were lower than those found in the plasma of patients with nonerosive RA, but not in those with erosive disease.…”
Section: Leptin and Autoimmunity M Vadacca Et Al 207mentioning
confidence: 91%
“…Recent work has shown that serum leptin levels can correlate with the level of inflammation. The concentration of leptin is elevated during active disease in rheumatoid arthritis patients, and it decreases when the disease is controlled [94][95].…”
Section: Leptin and Inflammationmentioning
confidence: 99%